Biomass Co-Firing for Electricity in Indonesia: A System Thinking Approach - Raisa Zakia; Yos Sunitiyoso (Eduvest - Journal of Universal Studies, 2025)
Indonesia's heavy reliance on coal for electricity generation poses significant environmental challenges, necessitating a transition toward more sustainable energy sources. Biomass co-firing, which involves blending biomass with coal in existing power plants, offers a practical solution  to  reduce  carbon  emissions  while  utilizing  the  country's  abundant  biomass resources. However, its large-scale implementation is influenced by multiple interdependent factors, including fuel availability, economic feasibility, technological readiness, and policy support. The study utilizes qualitative data analysis which is collected on interview sessions with   energy   and   electricity   stakeholders,   including   government,   national   electricity producers,  and  biomass  suppliers.  The study  found  44  factors  influence  the  system  of biomass co-firing for  electricity,  which  derived from seven categories, including biomass related  factors,  economic  feasibility,  government,  institutional  characteristics,  technical practicality, and new renewable energy/bioenergy. The interrelationships within the factors were analyzed using causal loop diagrams, which include three major drivers, which are technical  practicality,  institutional  characteristic,  and  economic  feasibility. The  findings emphasize  the  need  for  coordinated  policies,  investment  in  biomass  supply  chains,  and stakeholder collaboration to enhance co-firing effectiveness. This study contributes to the understanding   of   biomass   integration   in   the   electricity   sector   and   offers   strategic recommendations to accelerate Indonesia’s sustainable energytransition